Middle-range theorizing on logistics customer service. Issue 1 (15th February 2018) - Pellathy, Daniel A.; In, Joonhwan; Mollenkopf, Diane A.; Stank, Theodore P.
Abstract : Purpose: The purpose of this paper is to illustrate how a systematic application of middle-range theorizing, which pays particular attention to contexts and mechanisms, can be used to extend current knowledge on logistics customer service (LCS) in a number of critical areas. Design/methodology/approach: The paper applies Stank et al. 's (2017) framework for middle-ranging theorizing in logistics to develop a research framework and agenda that can guide future LCS research. Results are generated through a review of the LCS literature and an application of the main concepts of middle-range theorizing. Findings: The paper outlines opportunities for middle-range research that would extend LCS knowledge in the areas of human and behavioral factors, time-based competition, supply chain complexity, and digitization and technological innovation. Research limitations/implications: Describing the main characteristics of middle-range theorizing and how middle-range theorizing can be fruitfully applied to LCS research should help to stimulate new knowledge creation in this important area of supply chain logistics management. Practical implications: By focusing on why and when questions, middle-range theorizing engages with the practical realities of LCS that interest managers and students. Middle-range theorizing moves researchers toward developing a detailed understanding of what actually has to change in order for desired LCS-related outcomes to occur and the contextual factors likely impacting the change process. The paper should, therefore, allow managers to better translate LCS theory into action. Originality/value: Middle-range theorizing remains new to the supply chain logistics field. The application of middle-range theorizing to LCS research, and logistics research more generally, demands new perspectives on established relationships with the potential to drive original research in areas most relevant to managers.